DIALOGICAL PERSPECTIVES IN THE STUDY OF COMMUNICATION - Mazur, Lucas (PINS-Psychology in Society, 2025)
Hook, D, Franks, B & Bauer, M W (eds) (2011) The social psychology of communication. Houndmills: Palgrave Macmillan. ISBN 978-0-230-24736-9 pbk. Pages xv + 371. As a collection of essays on the psychological study of human communication, The social psychology of communication is rich in differing and often even competing theoretical perspectives and practical applications, and yet it also manages to be a book of singular purpose. As stated in the introduction, the goal of this collection is to “defamiliarize” the reader with regard to human communication to a sufficient extent so as to encourage fresh reflection on everyday social psychological processes. In this way the editors are suggesting the value of what they call an interfield approach to the study of communication, a marketplace of ideas in which multiple perspectives are encouraged without the prerequisite of a meta-theory smoothly linking them all. The book's 15 chapters cover a wide range of topics, theoretical schools of thought and areas of applied research. By exploring communication from so many thought-provoking angles, the collection succeeds in presenting the social psychological study of communication as a diversified field, one that has seen many accomplishments over the past few decades, and one that continues to be pregnant with questions and debates calling for further research.